Pelatihan dan Pendampingan Teknis Perawatan Pompa Sumur Dalam di Desa Luthu Lamweu, Kecamatan Sukamakmur, Kabupaten Aceh Besar, Provinsi Aceh - Zulfadhli; Husni; Sabri; Muhibbuddin; Dandi Bahtiar (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
This community service aims to improve care, maintenance and repair of submersible water pumps spread across Gampong Luthu Lamweu, Aceh Besar Regency, Aceh Province. Activities begin with the preparation stage, site feasibility survey, identification of problems with partners, implementation of activities, as well as socialization and evaluation of results. Problem identification is carried out through maintenance, upkeep and repair steps for water pumps, which are delivered through training and technical assistance by the PKM implementation team to participants, with the aim of ensuring that participants are able to independently manage and maintain the water pump system. The repair process focuses on components that can be repaired, while for damaged components, they are replaced with new spare parts. Evaluation is carried out at the final stage of activities to ensure that the water pump is functioning optimally and water distribution is running normally, so that the availability of water for agricultural and rice field needs can be guaranteed. This activity was carried out successfully, as evidenced by the appreciation received from the participants, especially local farmer groups, which showed their level of satisfaction and pride in their success in independently managing the maintenance and repair of water pumps.